A study on the preparedness and response of oil spill in Tanjung Perak Port, Surabaya (Case study: PT. Lamong Energi Indonesia) - Bimantoro, Rafly Ramadhan; Alam, Mochammad Helga Fairuuz (UIN Sunan Ampel Surabaya, 2024)
Tanjung Perak is a bustling port with significant shipping and loading/unloading activities, which can contribute to marine environmental pollution, including oil spills. These spills have serious impacts on the marine ecosystem, as oil spreads based on water conditions once released into the environment. Therefore, effective oil spill response measures are essential to mitigate the adverse effects of such incidents. This study aims to assess the preparedness of the Oil Spill Response (OSR) team at PT Lamong Energi Indonesia in preventing and controlling oil spills at Tanjung Perak Port. Conducted from February to April 2023, the research involved 15 members of the OSR operations team at PT Lamong Energi Indonesia as respondents. Data analysis utilized index analysis based on four key preparedness parameters: 1) knowledge and attitudes, 2) emergency response plans, 3) early warning systems, and 4) resource mobilization capacity. The results revealed that the OSR team's preparedness index was 75, indicating a